IOT DEVICES ORCHESTRATION USING BUSINESS PROCESS ENGINE - Jonathan, Ivan
Lately, the use of the internet of things (IoT) technology in this life has rapidly increased. This happens because of the need for automation that is increasingly needed in this digital era. The technology of IoT intends to combine the object of the “things” in daily life through the “internet” network. Technology and platform to automate processes involving IoT devices is already exist, one of the examples that is task automation service. However, it is still limited because only handles simple processes and cannot handle complex sensor event. In this final project, the result is an architectural model that utilizes the BPMN on BPMS technology, which is in charge of executing the IoT process. Complex Event Processing is used to handle the event from the sensors subscribed to by the process engine. As the case study for implementing this architecture, the smart irrigation case, an IoT system that aims to automate the irrigation process on arable land was selected. The implementation of the case study includes two processes, that is the process for carrying out the irrigation and the process for checking the availability of water in the tank for watering plants. Then, testing is carried out with various predefined test scenarios. In conclusion, the architecture built can properly orchestrate the IoT for the Smart Irrigation case study. Other than that, the use of BPMS on IoT has advantages, that is, the process will run dynamically following the condition of the physical environment, the BPMN diagram makes it easier for the user to understand the IoT process flow better, and this model also allows integration into the external non-IoT system.